Genreology in national linguistics: scientific school o f Floriy Batsevych - Dergach, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article summarizes the ideas of linguistic genreology in the context of the philological interpretation of the genre's nature. It is determined that the linguistic objectivity of its analysis is based on the ideas of communicative studies. In Ukrainian linguistics, they are systematically represented in the researches of the scientific school of F. Batsevych. The thesis is argued that his ideas that are related to the linguistic interpretation of the genre, its characteristics and communicative dominants, take into account, first of all, different forms and formats of intentions. The author's comment is given on their verbalization in dynamically changing variants as peculiar patterns of communicative situations, typed structure fixed by cultural tradition, as well as the fact that they acquire individual characteristics in the process of communication. It also defined that F. Batsevych emphasizes on the tactics of implementing of communicative strategies, which are interpreted as separate genres in micro-contexts.It is summarized that the research ideas of F. Batsevych in Ukrainian linguistics have developed into a consistent tradition, realized in the works of his colleagues. It allows us to talk about the formation and active functioning of an authoritative scientific school of linguistic genreology. It was determined that the concept of linguistic genreology, formed and systematically implemented by F. Batsevych in the author's texts and researches of his followers, generalizes the communicative dominants of the genre, which are based on extralinguistic parameters: social conditioning, typicality of the communicative situation, formal features, functionality, stability and variability.It is argued that F. Batsevych's linguistic ideas of genre analysis are meaningfully correlated with the objectivity of media genreology (in the context of functional parallelism with linguistic genreology). It was determined that its prospects lie in the implementation of methodological syncretism of the analysis of language in the dynamics of social communication and its functions in the media, in the emergence of invariant forms and methods of verbal mass interaction, in the motivated renewal of its stylistics and genre system. And this, in turn, determines the vectors that leadto the perspective of the ideas of neolinguistic research.
Keywords: F. Batsevych, genre, genreology, linguistic genreology, media genreology, communicative linguistics, functional stylistics, media linguistics, neolinguistics.